Biomedical Literature Dynamics - Kraft, D. H.; Polacsek, R. A. (Methods of Information in Medicine, 1974)
This paper outlines the objective, background, rationale, specific aims, methods of procedure, and significance of a proposed research effort to develop a model of biomedical literature dynamics for study and use. Based on existing knowledge of the documentation process, the model would incorporate the factors of growth, obsolescence, and scattering of the biomedical journal literature, in terms of productivity and usage. The model could then be used, upon confrontation with data, to understand the variations in the dynamics of the bodies of literature in several biomedical disciplines. Several factors, such as discipline size and age, would be considered in the analysis of this variance. Finally, the model would be used as a basis for the consideration and comparison of several existing simple decision models, related to collection development and location in biomedical libraries.
Keywords: Research Methodology; Library Operations Research; Biomedical Literature Dynamics; Biomedical Journal Selection and Disposition